Political and legal challenges in a Mars colony. (November 2016) - Szocik, Konrad; Lysenko-Ryba, Kateryna; Banaś, Sylwia; Mazur, Sylwia
Abstract: In our essay we are going to briefly discuss some legal and political questions associated with the future colonization of Mars which is now being planned by NASA and the second one is known as Project MarsOne. We assume that it will be unclear as to which legal and political solutions could work in the new Martian ecological niche. Here we will show that this issue requires more attention because we unable to predict which elements of human nature will dominate the lives of the Mars colonizers.